The BRIDGING project – citizenship, partnership and holistic development - Joanna Ludwika Pękala; Kamila Wichrowska (Problemy Wczesnej Edukacji)
The aim of the text is to introduce BRIDGING, an international project that involves professionals working in educational institutions (kindergarten, school or crèche), academic and cultural institution from Poland, Portugal, Finland and Belgium. The project aims to improve the quality of practices in early childhood education through participation of children, teachers, cultural and academic staff in artistic projects in public spaces. Crucial part of BRIDGING is to promote various ways of communication of children and adults using the concept of citizenship in the context of holistic approach. Additionally our intention is to introduce the preliminary results of the first Polish part of the BRIDGING project research. The study was conducted to investigate how the project is perceived by kindergarten teachers. Although only the first results are presented here, it is already quite evident what the specific areas of teachers’ sense of vocational self-efficacy are. The results show that our respondents value the experiences brought to them by the project. In their opinion BRIDGING gave them an opportunity to acquire knowledge about their city, neighbourhood and the partners’ countries. They also stated that the project has improved their skills of using ICT tools and various art techniques.